Remembering Cremutius Cordus: Tacitus on History, Tyranny and Memory - Wisse, Jakob (Histos, 2013)
Tacitus’ account of the treason trial of the historian Cremutius Cordus under Tiberius has long been recognized as a statement about the freedom of speech of a historian under a repressive regime. This paper offers a full interpretation of the passage, Annals 4.34–5, seen as part of the tightly woven texture of the beginning of the work. Its main problem is the perceived implausibility of Cremutius’ claim that his praise of Brutus and Cassius ought not to have provoked the emperor’s anger. It is here argued that this can be solved by a new interpretation of the preceding digression on historiography under the empire, a passage often assumed to expose the disingenuousness of Cremutius’/Tacitus’ claim; the concept of figured speech, often invoked, is shown to be irrelevant to the issue. Moreover, as it memorializes Tiberius’ guilt as well as Cremutius’ courageous frankness, the passage is a demonstration of the power of history, in accordance with the programmatic statement in 3.65.1.